Characterization of [123I]FP‐CIT binding to the dopamine transporter in the striatum of tree shrews by quantitative in vitro autoradiography. Issue 10 (14th July 2015) - Geisler, Stefanie; Beindorff, Nicola; Cremer, Markus; Hoffmann, Kerstin; Brenner, Winfried; Cumming, Paul; Meyer, Philipp T.; Langen, Karl‐Josef; Fuchs, Eberhard; Buchert, Ralph
ABSTRACT Objectives Aim of this study was to quantify the binding of [123I]FP‐CIT in striatum of healthy tree shrews. [123I]FP‐CIT is widely used in clinical SPECT imaging to reveal nigrostriatal degeneration in aid of the diagnosis of clinically uncertain parkinsonian syndromes. Despite its wide clinical use, the saturation binding parameters of [123I]FP‐CIT for the dopamine transporter (DAT) have not yet been determined in any mammalian brain. Tree shrews are genetically and neuroanatomically more similar to humans than are rodents and might therefore be a valuable animal model for research of neurological disorders involving brain dopamine. Experimental Design Quantitative in vitro autoradiography with [123I]FP‐CIT was performed with brains of healthy tree shrews and, for comparison, brains of healthy rats. Dopamine D2/3 receptor autoradiography with [3H]raclopride was also performed. Principal observations Saturation analysis revealed high specificity of [123I]FP‐CIT for DAT in the striatum with considerably higher affinity in tree shrews than in rats (KD = 10.3 versus 36.4 nM). The density of DAT binding sites also was higher in tree shrews than in rats (Bmax = 2499 versus 1495 pmol/g wet weight (ww)). [3H]raclopride revealed D2/3 receptors in the tree shrew striatum with about the same density as in rats (Bmax = 78.4 versus 84.1 pmol/g ww), but with slightly lower affinity in tree shrews (KD = 1.27 versus 0.59 nM). Conlusions The higher affinity in combination with the higher abundance of DAT binding sites compared to rat striatum predicts substantially higher binding of [123I]FP‐CIT in SPECT studies of living tree shrews. Synapse 69:497–504, 2015. © 2015 Wiley Periodicals, Inc.